Investigation of torsional behavior of polymer composite golf shaft. (2017) - Vijaya Ramnath, B.; Elanchezhian, C.; Deepak, M.; Narayan, Arvind
Abstract: Generally, two or more components used in distinct materials combined together to form the composite materials. These are special materials with vast varying properties. The automotive, aero space, sports industries and some of structures are made better by using composite materials due to its unique strength and hardness. Nowadays sports utilities are made of composites as one to make the golf shaft. This work aimed to fabricate Polypropylene - GRFP based golf shaft instead of normally used steel shafts. Torsion test was performed to look closely to know the power withstand by the composite golf shaft.